1948
DOI: 10.2307/1538202
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Thiourea and Phenylthiourea Upon the Development of Eleutherodactylus Ricordii

Abstract: The leptodactylid toads of the genus Elcuthcrodactylus are unusual among anurans in that they lay large-yolked, unpigmented, terrestrial eggs and have no aquatic larval stage. The embryology of one member of this group, the Jamaican species E. nubicola, has been described in some detail (Lynn, 1942) and it was Lynn, W Gardner. 1948. "THE EFFECTS OF THIOUREA AND PHENYLTHIOUREA UPON THE DEVELOPMENT OF ELEUTHERODACTYLUS RICORDII." The Biological bulletin 94, 1-15.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

1949
1949
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 24 publications
(20 reference statements)
1
23
0
Order By: Relevance
“…None of these factors appear to be associated with the eye size reduction, suggesting that it may be a specific effect of PTU treatment. In fact, such an effect on eye size reduction has been documented in frogs [8], [35], but has not been further studied. The current study describes the characterization of the effect of PTU treatment on eye development in zebrafish.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…None of these factors appear to be associated with the eye size reduction, suggesting that it may be a specific effect of PTU treatment. In fact, such an effect on eye size reduction has been documented in frogs [8], [35], but has not been further studied. The current study describes the characterization of the effect of PTU treatment on eye development in zebrafish.…”
Section: Introductionmentioning
confidence: 98%
“…In rats, it has been demonstrated that the administration of PTU through feeding and/or intraperitoneal injection can cause both acute and chronic toxicity [30]. Interestingly, the studies on rats have also led to the original discovery of thyroid hypertrophy and in turn the goitrogenic effect of PTU [31], [32], which has been subsequently confirmed in studies of the frog [8]. In zebrafish, it has been shown that treating zebrafish larvae with 0.003% PTU can suppress thyroid hormone (T4) immuno-reactivity in thyroid follicles [33].…”
Section: Introductionmentioning
confidence: 99%
“…The skull: Development of the skull is similar to that illustrated by Lynn (1942) for 4 days pre-hatching to 10 days post-hatching E. nubicola. A number of tooth buds were present on the maxillary-premaxillary arc.…”
Section: Microanatomy Of the Adult Reproductive Systemsmentioning
confidence: 64%
“…The upper part of the duct is lined with a ciliated and secretory epithelium (Fig. The froglets.-There are in the literature a number of descriptions of development through 125 metamorphosis in several species of direct-developing Eleutherodactylus and its relatives, such as Hylactophryne (Adamson et al, 1960;Bogert, 1969;Chibon, 1960;Gitlin, 1954;Goin, 1947;Jameson, 1950;Lutz, 1944Lutz, , 1948Lynn, 1942Lynn, , 1948Lynn andLutz, 1946, 1947;Sampson, 1904;Valett and Jameson, 1961) of which Lynn (1942) has presented the most complete. There is an abrupt transition to a non-secretory columnar epithelium low in the convoluted part of the duct (Fig.…”
Section: Microanatomy Of the Adult Reproductive Systemsmentioning
confidence: 99%
“…These changes correspond to thyroid gland maturation (Dent, 1942) and apparently rely on increased levels of circulating thyroid hormone (Lynn, 1947). It has been proposed that the ''larval program has been completely eliminated'' in the direct developing plethodontids (Alberch, 1989).…”
Section: Lost Larval Features?mentioning
confidence: 99%